Meat Quality of Female Post-Weaning Fat-Tailed Sheep with Docking and Level of Feeding Concentrate from Water, Fat and Protein Content (Jurnal Ilmu dan Teknologi Hasil Ternak, 2009)
Â  The objective of this experiment was to evaluate meat quality of female post-weaning fat-tailed sheep with docking and level of feeding concentrate from water, fat and protein content. The material used in this experiment was meat of 20 female post-weaning fat-tailed sheep from biceps femoris. Feeds given were elephant grass (Pennisetum purpureum) and concentrate â€œGemuk Aâ€. The sheep was house individually in a 0.75 x 1.0 m2 elevated house unit. The method was experiment with Nested Block Randomised Design, with treatmen of docking (D1) and non-docking (D0) and level of feeding concentrate (p), i.e. 1 percent (PO) and 3 percent (P2).The result showed that docking gave no significsntly difference (P>0.05) for water content, but for fat and proten content gave very significantly difference (P<0.01). Level feeding of concentrate gave no significantly difference (>0.05) for water content, but gave very significantly difference (P<0.01) for fat and protein content.In the average water content was 72.46; 72.77; 73.40 and 72.98 percent respectively, fat content 3.97; 5.76; 5.01 and 7.28 percent respectively and protein content 16.35; 17.75; 17.34 and 18.84 percent respectively.It could concluded that docking and level feeding of concentrate significantly increased fat and protein contents of meat of female post weaning fat-tailed sheep, but not significantly effect on water content. Docking and level of feeding concentrate at 3 percent of body weight should be considered to get good qualityy of female post weaning fat-tailed sheep from fat and protein content. Keywords: Meat Quality, Female Post-Weaning, Fat-Tailed Sheep, Docking